THE EFFECT OF DEBATE TECHNIQUE ON GRADE XI STUDENTS’ ACHIEVEMENT IN SPEAKING - Daud Hamonangan Hasibuan and Sri Minda Murni (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study aims to discover the effect of debate technique on grade XI students’ speaking achievement. It was conducted by using experimental research design. The population of this research was the elepent ( XI ) grade students of MA Swasta Robitotul Istiqomah Huristak. The samples of the research were two classes which consisted of experimental and control group which were chosen by using random sampling technique. They are consist of 57 students. The experimental group was taught by using Debate Technique, while the control group was taught without using Debate Technique. After analyzing the data, it was found that the value of tobserved was 0,13 with the degree of freedom (df)=55 at the level of significance a(0,05) = 2,004. It means that tobserved was lower than ttable (0,13>2,004). The result of this study showed that Debate Technique was not significantly affect on students’ speaking achievement.